ИССЛЕДОВАНИЕ ВЛИЯНИЯ КОРМОВ C БИОЛОГИЧЕСКИ АКТИВНЫМИ ДОБАВКАМИ НА РОСТ ОСЕТРОВЫХ РЫБ ПРИ БАССЕЙНОВОЙ ТЕХНОЛОГИИ ВЫРАЩИВАНИЯ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In article results of experiment on influence of forages with biologically active additives on growth and an exit russian and Siberian sturgeons are reflected at basin conditions of cultivation. the received results have shown advantage of mixed fodders with additives, such as clorella and a vitamin additive, at feeding of sturgeon fishes that was reflected in improvement of rybovodno-biological indicators young sturgeon fishes.